Crosstalk Between the Intratumoral Microbiota and the Tumor Microenvironment: New Frontiers in Solid Tumor Progression and Treatment - Qing Zhou; Lijun Zhou; Xi Chen; Qiuyan Chen; Lu Hao (Cancer Reports)
ABSTRACT Background The microbiota plays a significant role in the tumor microenvironment, and its impact on tumor development and treatment outcome cannot be overlooked. Thus, it is essential to comprehend the interactions between the microbiota and the tumor microenvironment. Recent Findings With the advent of next‐generation sequencing, microbiota research has advanced significantly in recent years. The interaction between the intratumoral microbiota and the tumor microenvironment is an emerging area of research that holds great promise for understanding and treating solid tumor progression. This crosstalk between the intratumoral microbiota and the tumor microenvironment is a complex process that involves a multitude of factors, including the immune system, cellular signaling pathways, and metabolic processes. The origin of the intratumoral microbiota differs between various solid tumor, and the quantity and diversity of intratumoral microbiota also fluctuate significantly within each solid tumor. Conclusion The aim of this review is to provide a detailed summary of the intratumoral microbiota in various types of solid tumors. This will include an analysis of their origins, differences, and how they impact the progression of solid tumors. Furthermore, we will emphasize the significant potential that the intratumoral microbiota holds for the diagnosis and treatment of solid tumors.